The impact of entry modes on export knowledge resources and the international performance of SMEs - Mogos Descotes, Raluca; Walliser, Björn (Management international / Gestiòn Internacional / International Management, 2010)
This research conceptualizes entry modes as forms of international experience that small and medium-sized enterprises (SMEs) gather and explores the role they play in building export knowledge and fostering international performance. Using a sample of 107 French SMEs from the steel industry, a causal model suggests that various entry modes have direct impacts on the level of explicit foreign market-related knowledge in SMEs and an indirect impact on tacit knowledge. Explicit and tacit knowledge correlate positively, and ultimately, an SME’s tacit knowledge regarding export markets improves its international performance.